The Maltese iguana : a novel [large type] - Dorsey, Tim (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"After a long and arduous COVID-19 quarantine, Serge A. Storms is fully vaccinated and ready to hit the road. Along with his condo neighbors, he cooks up a wild plan to celebrate in true Serge fashion: each week, they rent a shuttle van and head out for funky Florida road trips and some serious revelry. Meanwhile, a CIA revenge operation down in Honduras goes very, very wrong. The local liaison hired to help with the mission is the only witness to the disaster, and the CIA quickly sets a black ops contractor on his trail to eliminate him. Forced to flee his home country, the witness lands in Miami with a new identity and passport. But the CIA is still on his tail, pushing him further and further south to the Florida Keys, where he runs into Serge's convoy. With Florida's most lovable serial killer involved, the real party is about to get started"--